Whole blood transcriptome analysis in dairy calves experimentally challenged with bovine herpesvirus 1 (BoHV-1) and comparison to a bovine respiratory syncytial virus (BRSV) challenge - O’Donoghue, Stephanie; Earley, Bernadette; Johnston, Dayle; McCabe, Matthew S.; Kim, Jae Woo; Taylor, Jeremy F.; Duffy, Catherine; Lemon, Ken; McMenamy, Michael; Cosby, S. Louise; Morris, Derek W.; Waters, Sinéad M. (Frontiers in Genetics, 2023)
Bovine herpesvirus 1 (BoHV-1), is associated with several clinical syndromes in cattle, among which bovine respiratory disease is of particular significance. Despite the importance of the disease, there is a lack of information on the molecular response to infection via experimental challenge with BoHV-1. The objective of this study was to investigate the whole-blood transcriptome of dairy calves experimentally challenged with BoHV-1. A secondary objective was to compare the gene expression results between two separate BRD pathogens using data from a similar challenge study with BRSV. Holstein-Friesian calves (mean age ± s.d. = 149.2 days ± 23.8 days; mean weight ± s.d. = 174.6 ± 21.3 kg) were either administered BoHV-1 inoculate (1×107/ml × 8.5 ml) (n=12) or were mock challenged with sterile phosphate buffered saline (n=6). Clinical signs were recorded daily from day (d) -1 to d 6 (post-challenge), and whole blood was collected in Tempus RNA tubes on d 6 post-challenge for RNA-sequencing. There were 488 differentially expressed (DE) genes (P <0.05, False Discovery rate (FDR) <0.10, fold change ≥2) between the two treatments. Enriched KEGG pathways (P <0.05, FDR <0.05); included Influenza A, Cytokine-cytokine receptor interaction and NOD-like receptor signalling. Significant gene ontology terms (P <0.05, FDR <0.05) included defence response to virus and inflammatory response. Genes that are highly DE in key pathways are potential therapeutic targets for the treatment of BoHV-1 infection. A comparison to data from a similar study identified both similarities and differences in the immune response to differing BRD pathogens.